PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PEMBIASAAN IBADAH DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN ADIARSA BARAT II KARAWANG - Hendra Asri Harahap; Khalid Ramdhani; Afiyatun Kholifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The importance of fostering students’ religious character amid the digital era, which influences students’ behavior and morals. Islamic Religious Education plays a vital role in instilling religious values through the practice of worship at school. This study aims to describe the process of fostering students’ religious character through the practice of worship in Islamic Religious Education at SDN Adiarsa Barat II. This study employs a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. The research subjects consist of Islamic Religious Education teachers, the school principal, and students. Data analysis utilizes the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing conclusions. The results of the study indicate that the development of students’ religious character is achieved through religious practice activities such as reciting prayers before and after lessons, reading the Qur’an, performing congregational Dhuha prayer, and implementing the 5S culture (smile, greet, address, polite, courteous). These habit-forming activities help foster students’ religious character traits, such as discipline, responsibility, good manners, social awareness, and the habit of worship. Islamic Religious Education teachers serve as mentors, motivators, and role models in instilling religious values in students. However, the process of fostering religious character still faces challenges, including the influence of gadget use and a lack of parental supervision at home.